Poetic Language and the Computer: A Corpus Stylistic Study of The Waste Land - Jaafar, Eman Adil (International Journal of Language and Literary Studies, 2021)
This study aims at proposing a methodology in analyzing one of the significant poems of the twentieth century, The Waste Land by T.S. Eliot. By means of applying the tools of the computer, namely; Wmatrix (Rayson 2003, 2008) and WebCorp Live (Birmingham City University). This paper seeks to examine whether corpus stylistics can be helpful in analyzing a single poem 2. Verifying the importance of corpus tools in interpreting poetic language. Moreover, this study attempts to examine key semantic domains, keywords, and concordances in the poem. This study proves that corpus tools are crucial in matters of saving time, reaching to accurate results and achieving much more objectivity than applying only the qualitative method in analyzing the data. Thus, it is recommended to integrate both methodologies (qualitative and quantitative) in the study of poetic language.